Respuesta :
Answer:
Step-by-step explanation:
3x - 2y = –9
3x−2y+2y=−9+2y
3x=2y−9/3x^3
=2y−9/3
x=2/3y−3
4x + 3y = 22
4x+3y+−3y=22+−3y
4x=−3y+22
4x4
=−3y+22/4
x=−3/4y+11/2
The solution of the given system of equations are x=1 and y=6
What is Linear equation?
An equation between two variables that gives a straight line when plotted on a graph.
Given,
3x - 2y = -9
4x + 3y = 22
Consider the first linear equation
3x-2y = -9
3x= -9+2y
x= [tex]\frac{-9+2y}{3}[/tex]
x=[tex]\frac{2}{3}y-3[/tex]
Substitute the values in the second linear equation
4([tex]\frac{2}{3}y-3[/tex])+3y=22
[tex]\frac{8}{3} y-12+3y=22\\\frac{17}{3}y=22+12\\ \frac{17}{3}y=34\\y=6[/tex]
Substitute the value of y in the first linear equation
3x-2y= -9
3x-2×6=-9
3x-12=-9
3x=3
x=1
Hence, Solution of the given system of equations are x=1 and y=6
Learn more about Linear equation here
https://brainly.com/question/11897796
#SPJ2